Entre cabarés, noites líricas e rádios porto-alegrenses: a trajetória do músico Roberto Eggers (1889-1984) - Kenia Simone Werner (2012)
The purpose of this work is to present the biography of musician Roberto Eggers (1899-1984) by analysing his insertion in the musical scene of the town of Porto Alegre. The analysis of the network of meanings created by Eggers through his professional activities was conducted using the concepts of « field » and « habitus » developed by Bourdieu in the 1970s, following the operations suggested by Loïc Wacquant (2005). The main source of documents used in this study was the collection gathered by Eggers throughout his professional life in Porto Alegre, which is located in the Historical Museum Visconde de São Leopoldo, in the town of São Leopoldo, Rio Grande do Sul. Because Eggers was professionally engaged in several spaces concomitantly, this study is divided in four chapters according to his different activities and functions, without following the chronological order. We expose and analyse his work in cinemas and cabarets, in lyrical concerts and in the towns radios as a player, conductor and composer. Two further chapters are dedicated to the two operas of his authorship, Farrapos and Missões.